The effect of chronic kidney disease on CYP2B expression and activity in male Wistar rats. Issue 3 (26th April 2019) - Kucey, Andrew S.; Velenosi, Thomas J.; Tonial, Nicholas C.; Tieu, Alvin; RaoPeters, Adrien A. E.; Urquhart, Brad L.
Abstract: Chronic kidney disease (CKD) is characterized by progressive reduction in kidney function over time. CKD affects greater than 10% of the population and its incidence is on the rise due to the growing prevalence of its risk factors. Previous studies demonstrated CKD alters nonrenal clearance of drugs in addition to reducing renal clearance. We assessed the function and expression of hepatic CYP2B enzymes using a rat model of CKD. CKD was induced in Wistar rats by supplementing their chow with adenine and confirmed through the detection of elevated uremic toxins in plasma. Liver enzymes AST and ALT were unchanged by the adenine diet. Bupropion was used as a probe substrate for hepatic CYP2B function using rat liver microsomes. The resulting metabolite, hydroxy‐bupropion, and bupropion were quantified by ultra‐performance liquid chromatography coupled to time‐of‐flight mass spectrometry. Level of mRNA and protein were determined by RT‐PCR and Western blot, respectively. The results of our study demonstrate that CYP2B1 is downregulated in a rat model of CKD. CYP2B1 mRNA level was significantly decreased (88%, P  <   0.001) in CKD relative to control. Similarly, maximal enzymatic velocity ( V max ) for CYP2B was decreased by 46% in CKD relative to control ( P  <   0.0001). Previous studies involving patients with CKD demonstrated altered bupropion pharmacokinetics compared to control. Hence, our results suggest that these alterations may be mediated by attenuated CYP2B hepatic metabolism. This finding may partially explain the alterations in pharmacokinetics and nonrenal drug clearance frequently observed in patients with CKD.